143 Stereotactic Radiosurgery for Skull Base Meningiomas: 20-year Long-Term Outcomes With Volumetric Analysis. Issue Volume 65:Issue CN(2018)Supplement 1 (16th August 2018) - Patibandla, Mohana Rao; Lee, Cheng-Chia; Addagada, Gokul C; Sheehan, Jason P
Abstract: INTRODUCTION: Stereotactic radiosurgery (SRS) has become an integral part in the treatment of benign intracranial tumors, including meningiomas. Previous studies have typically used single diameter measurements when reporting outcomes, which can yield misleading results. The authors describe the use of SRS in the treatment of WHO grade I PFMs and correlate volumetric analysis with long-term outcomes. METHODS: This study is a retrospective analysis of a prospectively maintained IRB-approved database. Inclusion criteria were a diagnosis of WHO grade I SM treated with single-session SRS and has a minimum of 3 follow-up MRI studies available. Volumetric analysis was performed on the radiosurgical scan and each subsequently available follow-up scan by using slice-by-slice area calculations of the meningioma and numerical integration with the trapezoid rule. RESULTS: The final cohort consisted of 377 patients, 76.4% (288) of whom were female, with a median age of 57 yr (12-88 yr). SRS was the primary treatment for 49.3% (186) of the patients, whereas 38.7% (146) had 1 resection before SRS treatment and 12% (45) had 2 or more resections before SRS. Tumor characteristics included a median volume of 4.7 cm 3 (0.1-54.8 cm 3 ) at treatment with a median margin dose of 14 Gy (6-35 Gy). The median clinical and imaging follow-ups were 79.5 (15-328) and 72 (7-298) mo, respectively. The actuarial progression-free survival rates at 5, 10, 15, and 20 yr were 98.6%, 94.4%, 84.6%, and 77.6%, respectively. Overall post-SRS new neurological deterioration 17.8% (n = 67). The clinical deterioration is related to the tumor progression ( P  < .001, 95% confidence interval [CI] 2.460-18.559, and OR: 6.756). Volumetric analysis demonstrated that a change in tumor volume at 3 yr after SRS reliably predicted a volumetric change and tumor control at 5 yr (R2 = 0.62) with a P  < .001 and at 10 yr (R2 = .062) with a P  = .002. CONCLUSION: SRS, as either upfront or adjuvant treatment, is a durable therapeutic option for WHO grade I SMs, with high tumor control and a low incidence of post-SRS neurological deficits. Lesion volumetric response at the short-term follow-up of 3 yr is predictive of the long-term response at 5 and 10 yr.